Classroom Action Research: Implementasi Model Picture and Picture in Social Learning in Elementary Schools - Alsokari, Tareq; Rahmatika, Nada; Herawati, Dewi; Kardinal, Kardinal; Yumna, Yumna (International Journal of Elementary School, 2024)
One of the factors that influences students' learning motivation is the use of appropriate learning media by teachers because media is a tool to convey the message of the material being taught. This research aims to analyze the effects of using multimedia in the learning process in elementary schools. This research uses quantitative methods with a classroom action research approach. Data sources were taken using questionnaires and oral tests from twenty-one students from one of the elementary schools in Indonesia. All data were analyzed using SPSS 18 software with descriptive analysis (percent). Overall statistical analysis shows that the use of the model Picture and Picture in social learning has shown encouraging results. This fact can be seen from the increase in students' pre-test and post-test scores which were carried out through two learning cycles. Even students show positive learning attitudes such as being happy, enthusiastic, and always active in learning. Therefore, pictures and pictures are one of the alternatives that teachers can use as a solution for social learning which has been considered boring and students get bored quickly.